The Principle of 'Correct Pronunciation': Teaching English as a Foreign Language in the Early Twentieth Century. (2nd January 2016) - Pedrazzini, Luciana
Abstract: Pronunciation took root as a theoretically founded discipline under the auspices of the Reform Movement at the end of the nineteenth century. The legacy of the Movement can also be discerned in the numerous manuals for the teaching of English as a foreign or second language published at the beginning of the twentieth century. This paper aims to concentrate on one of the main principles promoted by the Movement, that is the primacy of speech, and consider how this principle was pursued through a practical methodology for the acquisition of 'correct pronunciation' in selected writings of some of the 'pioneers' in the developing English as a Foreign Language (EFL) teaching field both in Europe and overseas. The analysis in this paper also aims to show how these applied linguists ante litteram had to gauge their prescriptive intentions of conveying appropriate pronunciation norms against the backdrop of new educational contexts and explore alternative avenues.